Use of the Alpha-Glucosidase Inhibitor Acarbose in Patients with ‘Middleton Syndrome’: Normal Gastric Anatomy But with Accelerated Gastric Emptying Causing Postprandial Reactive Hypoglycemia and Diarrhea - Raymond J Playford; Charlotte Pither; Rui Gao; Stephen J Middleton (Canadian Journal of Gastroenterology)
Postprandial reactive hypoglycemia, early satiety and diarrhea are well-recognized side effects following full or partial gastrectomy or gastric bypass. It has only recently been realized, however, that patients with normal gastric anatomy may experience similar symptoms and signs due to primary accelerated gastric emptying (Middleton syndrome). In previous case studies, patients responded well to the use of dietary modification (frequent small-volume meals) alone. The authors describe two patients with this syndrome who continued to experience symptoms of reactive postprandial hypoglycemia despite dietary intervention but became asymptomatic following the addition of the alpha-glucosidase inhibitor acarbose.